Reconocimiento a Eduardo Oliva por sus valiosos aportes a la institución - Carpio, Analia Lorena; Carrizo, Hugo; Fernandez Valdes, María; Giannini, Maximiliano Luis; González, Mario; Leiva, Sergio Dante; Nieto, Carla Lorena; Rettore, Hector Armando (Estación Experimental Agropecuaria La Rioja, INTA, 2023)
EEA La Rioja